Pengaruh Kontribusi Pajak Kendaraan Bermotor dan Bea Balik Nama Kendaraan Bermotor Pada Pendapatan Asli Daerah - Kardevi Rakatitha, Putu Nadya; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 21 No 2 (2017), 2017)
Tax is a tool for the government in achieving the objective of obtaining both direct and indirect receipts to finance routine expenditure as well as national and economic development of the community. Regional Tax and Regional Retribution is one of the most important sources of income to finance the implementation of regional government and regional development in order to secure autonomy in a wide, tangible and responsible area. One type of local taxes are tax  vehicle and cost  of  vehicle . This study aims to examine the effect of tax vehicle on l ocally-generated  revenue , and the cost of vehicle refund on l ocally-generated  revenue . The data used are secondary data that uses time series from 2013 to 2016, using documentation method done at Bali Province Income Board. Sampling method used is non probability sampling method with purposive sampling technique. Data analysis used in this research is multiple linear regression analysis. The result of the analysis shows that the contribution of tax vehicle has a positive effect on the l ocally-generated revenue and the average contribution value is 31.94 percent, then the contribution of cost of vehicle also states a positive effect on the l ocally-generated  revenue with the average value of its contribution is equal to 39.55 percent.